2021
DOI: 10.1186/s13287-021-02387-6
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles containing miR-146a-5p secreted by bone marrow mesenchymal cells activate hepatocytic progenitors in regenerating rat livers

Abstract: Background Small hepatocyte-like progenitor cells (SHPCs) appear to form transient clusters in rat livers treated with retrorsine (Ret) and 70% partial hepatectomy (PH). We previously reported that the expansion of SHPCs was amplified in Ret/PH-treated rat livers transplanted with Thy1+ cells derived from d-galactosamine-treated injured livers. Extracellular vesicles (EVs) produced by hepatic Thy1+ donor cells activated SHPCs via interleukin (IL)-17 receptor B signaling. As bone marrow-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 50 publications
1
37
0
1
Order By: Relevance
“…Previous research indicated that EVs cargos can play important role in modulating the recipient cell behavior in liver disease. Ichinohe et al 35 indicated that miR-146a-5p is involved in the production of EVs by BM-MCs, may play a major role in accelerating liver regeneration. Similarly, our results showed that the downregulated hPMSCs-EVs circ-RBM23 suppresses hepatocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicated that EVs cargos can play important role in modulating the recipient cell behavior in liver disease. Ichinohe et al 35 indicated that miR-146a-5p is involved in the production of EVs by BM-MCs, may play a major role in accelerating liver regeneration. Similarly, our results showed that the downregulated hPMSCs-EVs circ-RBM23 suppresses hepatocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Clusters of SHPCs in recipient livers were collected by using laser microdissection, following the manufacturer's protocol [22,30]. Total RNA was isolated from the captured cells using the RNeasy Mini Kit (Qiagen, Hilden, Germany).…”
Section: Laser Microdissection and Gene Expression Analysismentioning
confidence: 99%
“…For miRNA expression analysis, miRNAs were transcribed into cDNA using the TaqMan MicroRNA Reverse Transcription kit (Applied Biosystems, Foster City, USA) and RT primers provided with the TaqMan miRNA assay (Applied Biosystems). The cDNA products were analyzed using TaqMan miRNA sequence-speci c probes for U6 small nuclear 2 (U6), miR-125b-5p, miR-145-5p, miR-199a-5p, miR-451-5p, miR-3473-5p, and let-7f, Premix Ex Taq (Takara), and the ABI Prism 7500 sequence detection system (Applied Biosystems) [30,31]. The primers used are listed in Supplemental Table 2.…”
Section: Laser Microdissection and Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These include the miRNA-183-5p and microRNA-221-3p that both have been assigned to the neuroprotective effects of BMSC EVs [ 111 , 112 ]. Their protective effects in ischemia/reperfusion injury are also not restricted to neuronal tissues as has been reported in the hepatocellular context but, apparently, are mediated by another non-coding RNA cargo, the miRNA-146a-5p [ 113 , 114 ]. Moreover, in mouse models, BMSC EVs induce VEGFR1 and -2 expression of endothelial cells and promote endothelial tube formation in vitro [ 115 ].…”
Section: Introductionmentioning
confidence: 99%